2008
DOI: 10.1021/ja8064717
|View full text |Cite
|
Sign up to set email alerts
|

Single Peptide Assembly onto a 1.5 nm Au Surface via a Histidine Tag

Abstract: Nanoparticle surfaces functionalized with proteins or other biomolecules provide a mechanism for interfacing the unique properties of nanomaterials with biological samples. In most of these studies, the biomolecule is conjugated to a gold nanoparticles (AuNP) surface through the thiol group of native or introduced cysteine residues. Here we demonstrate the direct attachment of a hexa-histidine tagged (His(6)) peptide to a 1.5 nm AuNP. Binding occurs via a specific interaction between the Ne of the His imidazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 38 publications
3
45
0
Order By: Relevance
“…Its use as a conjugation strategy is still somewhat limited, because it requires direct access of the imidazole residues to the inorganic surface of the nanocrystals, although it has been gaining interest in the past few years. 159,162,223,224 The original azide-alkyne Huisgen cycloaddition reaction requires a copper catalyst in particular when using alkyne-modified molecules. 225,226 It has been applied to non-fluorescent NPs such as Fe 3 O 4 nanocrystals.…”
Section: Bioconjugation To Target Moleculesmentioning
confidence: 99%
“…Its use as a conjugation strategy is still somewhat limited, because it requires direct access of the imidazole residues to the inorganic surface of the nanocrystals, although it has been gaining interest in the past few years. 159,162,223,224 The original azide-alkyne Huisgen cycloaddition reaction requires a copper catalyst in particular when using alkyne-modified molecules. 225,226 It has been applied to non-fluorescent NPs such as Fe 3 O 4 nanocrystals.…”
Section: Bioconjugation To Target Moleculesmentioning
confidence: 99%
“…In solution at pH 7.4, rec1-resilin is hydrophilic and negatively charged and the pH value is much higher than the pKa of 4.5 for Asp that initiates interaction between the COOe groups on the peptide side chain and the surface anchors to the gold surface. The broad but weak positive feature observed from 1240 to 740 cm À1 region at this pH may be related to the interaction of Au with His residue [53]. In neutral and basic pH imidazole nitrogen in His residues is in the deprotonated state and can interact with the protein.…”
Section: Molecular-level Characterization Of the Interactions Of Rec1mentioning
confidence: 79%
“…Si et al [52] employed synthetic oligopeptides containing redox-active Tyr residues to prepare gold and silver nanoparticles. Kogot [53] and Johnson [54] reported control of protein orientation at interfaces using histidine residue. Fig.…”
Section: Molecular-level Characterization Of the Interactions Of Rec1mentioning
confidence: 99%
“…4). It was reported that a hexahistidine tag (His-tag) of protein binds on the surface of AuNPs through metal-histidine coordination444546. When a stabilizing agent is small and weakly binds on the surface of AuNPs such as citrate, a protein with a His-tag easily binds to Au surface46.…”
Section: Resultsmentioning
confidence: 99%